Análise faunística de Cicadellidae (Insecta: Homoptera) em área de Mata Atlântica - Coelho, Luci Boa Nova (Universidade Federal de Viçosa, 1997)
Com base em coletas de armadilha luminosa, realizadas de 1981 a 1993, na Mata do Paraíso (20°46 -20°48 S; 45°50 -45°52 W), reserva de Mata Atlântica situada no município de Viçosa, Estado de Minas Gerais, foi obtido o total de 10.809 espécimes de cigarrinhas da família Cicadellidae (Homoptera), distribuídos em 11 subfamílias: Agalliinae, Cicadellinae, Coelidiinae, Deltocephalinae, Gyponinae, Iassinae, Idiocerinae, Neocoelidiinae, Nirvaninae, Xestocephalinae e Typhlocybinae, esta última não estudada em nível de gênero e espécie. Neste trabalho, são listados 62 gêneros determinados e 156 espécies, das quais 37 são novas para a ciência e 10 são pela primeira vez registradas para o Brasil. Também foram registradas 49 novas ocorrências para Minas Gerais e 58 para Viçosa. Chaves taxonômicas ilustradas para identificação das subfamílias, das tribos e dos gêneros são apresentadas. As variações sazonais na abundância e riqueza dos táxons foram analisadas. Flutuações anuais das populações foram relacionadas à variação da temperatura e da pluviosidade na localidade. A estrutura faunística diferiu entre as estações chuvosa e seca da Mata do Paraíso. Dentre as espécies mais representativas, Xestocephalus desertorum (Berg, 1879), X. ancorifer Linnavuori, 1959 (Xestocephalinae), Planicephalus flavicosta (Stal, 1860), Graminella striatella Linnavuori, 1959, Balclutha sp. 1 (Deltocephalinae), Plesiommata corniculata Young, 1977 e Hortensia similis (Walker, 1951) (Cicadellinae) foram significativamente mais abundantes nas estações chuvosas; Curtara atomaria (Stal, 1862) (Gyponinae) e Balclutha hebe (Kirkaldy, 1906) não sofreram diferenças significativas na abundância entre as estações.

Based on light-trap collections from 1981 to 1993 at Mata do Paraíso (20°46 -20°48 S; 45°50 -45°52 W), a tropical forest environment at Viçosa county, Minas Gerais State, Brazil, a total of 10,809 specimens of leafhoppers (Homoptera: Cicadellidae) were counted, belonging to 11 subfamilies: Agalliinae, Cicadellinae, Coelidiinae, Deltocephalinae, Gyponinae, Iassinae, Idiocerinae, Neocoelidiinae, Nirvaninae, Typhlocybinae and Xestocephalinae. Genera and species of Typhlocybinae were not identified. In this work are listed 62 determined genera and 156 species. Among the species 37 of them new to science and 10 are recorded for the first time to Brazil. It was also found 49 new records from Minas Gerais and 58 from Viçosa. Illustrated taxonomic keys for identification of subfamilies, tribes and genera are presented. Within and between-year fluctuations in abundance and richness of the leafhoppers were analyzed. Annual fluctuations in the population were related to local temperature and rainfall patterns. Wet season faunal structure was different from that of the dry season at Mata do Paraíso. Among the more representative species Xestocephalus desertorum (Berg, 1879), X. ancorifer Linnavuori, 1959 (Xestocephalinae), Planicephalus flavicosta (Stal, 1860), Graminella striatella Linnavuori, 1959, Balclutha sp. 1 (Deltocephalinae), Plesiommata corniculata Young, 1977 and Hortensia similis (Walker, 1951) (Cicadellinae) were significantly more abundant during the wet seasons; Curtara atomaria (Stal, 1862) (Gyponinae) and Balclutha hebe (Kirkaldy, 1906) showed no difference between wet and dry seasons.
Faunistic survey of Cicadellidae (Insecta: Homoptera) in a Atlantic forest environment
Keywords: Biodiversidade; Cicadellidae; Insecta; Biodiversity; Cicadellidae; Insecta; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA